Neutrophil-To-lymphocyte ratio as a biomarker for clinical response after autologous haematopoietic stem cell transplantation in systemic sclerosis - Keret, Shiri; Kaly, Lisa; Schett, Georg; Bergmann, Christina; Feldman, Erik; Zuckerman, Tsila; Yehudai-Ofir, Dana; Shouval, Aniela; Awisat, Abid; Rosner, Itzhak; Rozenbaum, Michael; Boulman, Nina; et al. (Rheumatology, 2025)
Objective: SSc is a complex disease that affects various target organs, making it difficult to assess response and determine remission or relapse. A baseline neutrophil-To-lymphocyte ratio (NLR) >2.95 is associated with severe progressive skin and lung disease and decreased 5-year survival in SSc. However, it is unknown whether NLR changes in response to treatment. To retrospectively evaluate NLR changes as a biomarker for treatment response in SSc. Methods: Progressive diffuse SSc patients who were treated with autologous haematopoietic stem cell transplantation (AHSCT group), with combination therapy of rituximab and MMF (combination group) or chimeric antigen receptor-T-cell (CAR-T) therapy group, were recruited along with healthy controls (HC group). NLR, modified Rodnan Skin Score (mRSS) and forced vital capacity (FVC)% predicted were repeatedly assessed over 2 years. Results: Fifteen patients were recruited in the AHSCT group, 15 in the combination group and 6 patients in the CAR-T group. Baseline mean NLR was high (>2.95) in AHSCT, combination groups and CAR-T compared with HC. All treatment arms showed a statistically significant decrease in mRSS values and an increase in FVC% at each time point up to 12 months. In a linear mixed model, NLR significantly decreased up to 24 months only in the AHSCT group. NLR correlated with mRSS and FVC exclusively in the AHSCT group. NLR increased above 3 in two patients who experienced a relapse after AHSCT. Conclusion: NLR is a simple biomarker that correlated with outcome measures in SSc following AHSCT but not with conventional therapy or CAR-T therapy. It is suggested that a decrease in NLR following AHSCT may indicate remission, whereas an increase may be associated with exacerbation. Further research is needed to validate these novel findings.
CRIS-Team Scopus Importer:2025-05-16
Keywords: autologous haematopoietic stem cell transplantation; biomarker; MMF; neutrophils-To-lymphocytes ratio; rituximab; SSc